Pancasila Education Learning Model Based on Cultural and Civic Literacy for Students’ Critical Literacy and Metacognitive Skills in Pancasila Education - Nirmayani, L. Heny; I Kadek Edi Yudiana (Universitas Pendidikan Ganesha, 2025)
Reading is a fundamental skill for first-grade students as the foundation of early literacy, cognitive development, and academic readiness; however, many elementary students are still unable to read or recognize the alphabet. This study aims to analyze a Pancasila education learning model based on cultural and civic literacy that is oriented towards critical literacy and students' cognitive abilities. The research uses the ADDIE development model with testing on aspects of validity, practicality, and effectiveness. The research subjects included subject matter experts, language experts, learning design experts, teachers, and 182 elementary school students. Data were collected through questionnaires, tests, and non-tests, then analyzed qualitatively through validator assessments and teacher responses, and quantitatively through validity tests, practicality tests, and effectiveness tests using MANOVA. The results showed that the developed model consisted of six main phases, namely stimulation, creative idea exploration, elaboration, presentation of results, confirmation, and appreciation, with the support of a model book and teaching modules. The validity test produced CVR and CVI values of 1, indicating a very high level of validity, while the practicality test obtained a score of 81.80, which is classified as very practical. Meanwhile, the effectiveness test with an N-Gain Percent of 49.58 indicates moderate effectiveness. The study concludes that the culture and citizenship literacy-based learning model is valid, practical, and effective in fostering global diversity character and improving Pancasila Education learning outcomes. Through this approach, students not only master academic content but also develop critical thinking, empathy, and the ability to apply tolerance values in real life.